External validation of a red cell-based blood prognostic score in patients with metastatic renal cell carcinoma treated with first-line immunotherapy combinations - Michele Maffezzoli; Matteo Santoni; Giulia Mazzaschi; Sara Rodella; Eleonora Lai; Marco Maruzzo; Umberto Basso; Davide Bimbatti; Roberto Iacovelli; Annunziato Anghelone; Ondřej Fiala; Sara Elena Rebuzzi; et al. (Clinical & Experimental Metastasis, 2024)
Immunotherapy combinations with tyrosine-kinase inhibitors (TKIs) and immune checkpoint inhibitors (ICIs) had significantly improved outcomes of patients with mRCC. Predictive and prognostic factors are crucial to improve patients’ counseling and management. The present study aimed to externally validate the prognostic value of a previously developed red cell-based score , including hemoglobin (Hb), mean corpuscular volume (MCV) and red cell distribution width (RDW), in patients with mRCC treated with first-line immunotherapy combinations (TKI plus ICI or ICI plus ICI). We performed a sub-analysis of a multicentre retrospective observational study (ARON-1 project) involving patients with mRCC treated with first-line immunotherapy combinations. Uni- and multivariable Cox regression models were used to assess the correlation between the red cell-based score and progression-free survival (PFS), and overall survival (OS). Logistic regression were used to estimate the correlation between the score and the objective response rate (ORR). The prognostic impact of the red cell-based score on PFS and OS was confirmed in the whole population regardless of the immunotherapy combination used [median PFS (mPFS): 17.4 vs 8.2 months, HR 0.66, 95% CI 0.47–0.94; median OS (mOS): 42.0 vs 17.3 months, HR 0.60, 95% CI 0.39–0.92; p < 0.001 for both]. We validated the prognostic significance of the red cell-based score in patients with mRCC treated with first-line immunotherapy combinations. The score is easy to use in daily clinical practice and it might improve patient counselling.